COMMUNITY SERVICE COMMUNITY EMPOWERMENT TO OVERCOME HYPERTENSION WITH A COMBINATION OF FOOT MASSAGE THERAPY AND ROSELLA FLOWER TEA AT THE POSYANDU FOR THE ELDERLY, SERANG DUSUN MEKARJAYA VILLAGE, PURWASARI DISTRICT, KARAWANG REGENCY - Desty Lismayanti,; Sarini, Sarini; Yanti Rosmayanti,; Sumitro, Sumitro; Okti Rahayu Asih,; Nining Sugihartati,; Yazin Azhari,; Cindy Destianty,; Mutiaraa Puspita Asih, (International Journal of Social Science, 2023)
Hypertension is an abnormal increase in blood pressure in the arteries that carry blood from the heart and continuously pump blood to all tissues in the organs of the body for a certain period of time, untreated hypertension sufferers have twice the chance of developing stroke and heart disease. Non-pharmacological drugs can be used as an alternative in reducing high blood pressure, one of which is a combination of foot massage and utilization of rosella flower tea. The purpose of this service is for community understanding of the combination of foot massage management and utilization of rosella flower tea to reduce hypertension. This service is carried out by mentoring and health education in groups. Educational material on how to do foot massage and processing rosella flowers into drinking water to reduce high blood pressure to 20 respondents from Serang Hamlet, Mekarjaya Village, Purwasari Sub-district. The results of the evaluation showed an increase in the understanding of residents, pre-test most of them did not understand as many as 14 people (70%), and post-test all respondents had good understanding (100%). The results of blood pressure measurements in the elderly with hypertension in the elderly with hypertension, pre-test showed most of the 1st degree hypertension as many as 10 people (50%), 2nd degree hypertension as many as 8 people (40%), 3rd degree hypertension as many as 2 (10%). Assistance and education are very useful to increase residents' understanding of foot massage and rosella flower tea processing to reduce hypertension levels non-pharmacologically